Quick Response Codes in Promoting Student-Centred Learning - Sriyuliyanti, Sriyuliyanti (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
This study was aimed to investigate the implementation of Quick Response Codes in improving student-centred learning and to find out some challenges faced by the learners while using the QR Codes. This study employed descriptive study design and a cross-sectional survey-based design. Two research tools were used, namely, questionnaires and interviews. The participants were 20 students at a private business high school (first grade) located in South Korea. The result of the study showed that students overwhelmingly expressed a positive attitude toward the use of Quick Response Codes (QR codes) in promoting student-centred learning. They perceived QR codes as effective tools for enhancing motivation, engagement, and accessibility to learning resources. The majority of students appreciated the autonomy and collaborative opportunities QR codes offer, contributing to increased participation and self-directed learning. Despite the challenges of varying motivation levels in group work and time constraints, students expressed a high agreement to continue using QR codes in future learning. This underscores the importance of teacher creativity and effective time management to maximize the positive impact of QR codes on student-centred learning. While the study acknowledges varied opinions, it underscores the significant role QR codes play in supporting a student-centric approach to learning.